PATTERN FORMATION DURING DEVELOPMENT OF THE EMBRYONIC CEREBELLUM - Hawkes, Richard (Frontiers in Neuroanatomy, 2012)
The patterning of the embryonic cerebellum is vital to establish the elaborate zone and stripe architecture of the adult. This review considers early stages in cerebellar Purkinje cell patterning, from the organization of the ventricular zone to the development of Purkinje cell clusters—the precursors of the adult stripes.